Existence and Characterization of Solutions of Nonlinear Volterra-Stieltjes Integral Equations in Two Variables - Mohamed Abdalla Darwish; Józef Banaś (Abstract and Applied Analysis)
The paper is devoted mainly to the study of the existence of solutions depending on two variables of a nonlinear integral equation of Volterra-Stieltjes type. The basic tool used in investigations is the technique of measures of noncompactness and Darbo’s fixed point theorem. The results obtained in the paper are applicable, in a particular case, to the nonlinear partial integral equations of fractional orders.